PEMANFATAAN TIK DALAM DIGITALISASI SEKOLAH UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI TK RAHMANIA KOTA SERANG - Eneng Ulfatullailah; Siti Nurhopipah; Ahmad Subagyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The utilization of information technology in early childhood education has become a pivotal factor in enhancing the quality of learning. This study examines the implementation of information technology and its impact on teaching methods in Rahmania Islamic Kindergarten, student engagement, and learning outcomes. By employing a qualitative research approach, including interviews, observations, and document analysis, this study identifies how digital tools, educational applications, and interactive media contribute to a more dynamic and effective learning environment. The results of the research show that the use of information technology at Rahmania Islamic Kindergarten Serang City has been implemented. With indications that, in planning the learning process, appropriate learning approach strategies for early childhood, learning content that is in accordance with the curriculum, and assessments to improve the quality of learning have been implemented using information technology infrastructure, However, challenges such as some teachers have not fully mastered the use of information technology, infrastructure limitations, and adaptation barriers must be addressed to maximize the benefits of technology in early childhood education. This research provides insights into best practices for implementing information technology in kindergarten to ensure meaningful and sustainable educational improvements.